PERBANDINGAN HASIL BELAJAR STAD DENGAN PROBLEM SOLVING DAN STAD TANPA PROBLEM SOLVING - Eka Yulianti; Trisnaningsih Trisnaningsih; Rahma Kurnia Sri Utami (JPG (Jurnal Penelitian Geografi), 2014)
This study aims to investigate : (1) The difference between learning outcomes of Geography at STAD learning model with problem solving and learning model STAD with no problem solving. (2) The difference between the increase (n with-gain) of Geography learning outcomes using STAD learning model with problem solving and learning model STAD with no problem solving. The research used a quasi-experimental method (Quasi Experimental Design). The population in this research were all students of class X which consists of two classes such as experimental class (X.1) and a control class (X.2). Data analysis used t test. The results are: (1) There are differences in geography learning outcomes using STAD learning model with Problem Solving higher than the learning outcomes of Geography students with learning model STAD without Problem Solving. (2) There are differences in the increase (n-gain) Geography learning outcomes with STAD learning model with problem solving and learning model STAD without Problem Solving.Penelitian ini bertujuan untuk : (1) Perbedaan hasil belajar Geografi pada model pembelajaran STAD dengan Problem Solving dan model pembelajaran STAD tanpa Problem Solving. (2) Perbedaan peningkatan (n-gain) hasil belajar Geografi menggunakan model pembelajaran STAD dengan Problem Solving dan model pembelajaran STAD tanpa Problem Solving. Penelitian menggunakan metode eksperimen semu (Quasi Experimental Design). Populasi dalam penelitian ini adalah seluruh siswa kelas X yang terdiri dari dua kelas yaitu kelas eksperimen (X.1) dan kelas kontrol (X.2). Analisis data menggunakan uji t. Hasil penelitian menunjukkan: (1) Ada perbedaan hasil belajar Geografi yang menggunakan model pembelajaran STAD dengan Problem Solving lebih tinggi dari pada hasil belajar Geografi siswa dengan model pembelajaran STAD tanpa Problem Solving. (2) Ada perbedaan peningkatan (n-gain) hasil belajar Geografi dengan model pembelajaran STAD dengan Problem Solving dan model pembelajaran STAD tanpa Problem Solving.Kata kunci: hasil belajar, problem solving, STAD